2016
DOI: 10.1021/acs.joc.6b01243
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of l-Pyranosides by Hydroboration of Hex-5-enopyranosides Revisited

Abstract: Extensive study of the diastereoselective synthesis of l-pyranosides utilizing hydroboration of substituted exo-glucals (5-enopyranosides) obtained from d-sugars is presented. On the basis of this study we present the empirical rules describing the reaction stereoselectivity and the correlation between the yield of the l-ido product and the size of protecting groups used. Application of these guidelines revealed that the hydroboration of methyl 2,3-O-methyl-6-deoxy-α-d-xylo-hex-5-enopyranoside resulted in excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…As expected, the corresponding d ‐glucoside 1 was formed as the major product, nevertheless, the desired l ‐ ido thioglycoside 4 was also obtained in 32 % isolated yield. Recently, Łopatkiewicz and Mlynarski have demonstrated that hydroboration stereoselectivity can be substantially influenced by the C4 protective group . They have found that small C4‐substituents or free 4‐OH group are favorable, while bulky C‐4 substituents are unfavorable for l ‐idose isomer formation.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the corresponding d ‐glucoside 1 was formed as the major product, nevertheless, the desired l ‐ ido thioglycoside 4 was also obtained in 32 % isolated yield. Recently, Łopatkiewicz and Mlynarski have demonstrated that hydroboration stereoselectivity can be substantially influenced by the C4 protective group . They have found that small C4‐substituents or free 4‐OH group are favorable, while bulky C‐4 substituents are unfavorable for l ‐idose isomer formation.…”
Section: Resultsmentioning
confidence: 99%
“…The C-5 epimerization of 26 was performed by hydroboration with BH 3 ·THF complex followed by oxidation with H 2 O 2 under previously optimized conditions, using 10 equiv. of the borane reagent [ 25 , 26 , 65 , 66 , 67 ]. Although the yield of the expected l - gulo -configured product 28 was only 53%, a sufficiently high l -guloside: d -mannoside ratio was observed ( 28 : 24 ~5:1), so it was considered worthwhile to investigate the C-5 epimerization of 1-thiomannoside alkenes having other protecting group patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to produce l -sugars from common carbohydrates by cost-effective and high-yielding synthetic routes. To meet the demand of l -sugars, various strategies have been developed for their synthesis [ 20 , 21 , 22 , 23 , 24 ], including C-5 epimerization of readily available d -sugars [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], homologation of carbohydrates with shorter chains [ 38 , 39 , 40 , 41 , 42 ], de novo synthetic routes [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], head to tail inversion [ 51 , 52 , 53 , 54 , 55 , 56 ], site selective epimerization [ 57 , 58 ], C-H activation [ 59 , 60 ], and enzymatic synthesis [ 61 , 62 ]. However, there are very few approaches that provide the l -sugars as glycosyl donors, e.g., in form of thioglycosides, ready for glycosylation [ 60 , 63 , 64 , 65 , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations